Design And Development Of L-Band Slotted Waveguide Antenna - Lim, Ka Sing (2004)
The goal of this research is to gain more insight in the design and development of slotted waveguide antenna. A post slot waveguide antenna consists of centerline longitudinal slot with a tuning post is considered due to its numerous advantages in broadcasting industry. Slot antenna arrays allow accurate control of aperture excitation amplitude and phase.